Detecting changes in along-path HF propagation during the April 2024 total solar eclipse with radio amateurs and low-cost instrumentation - Usis, Maris; Goodman, Adam; Schwartz, Laura; Kazdan, David; Collins, Kristina; Gibbons, John; Sastry, Shashank; Ayres, Lucy; Brault, Christopher; Byas, Seth; Dompke, Michael; Dowell, Michelle; et al. (Frontiers in Astronomy and Space Sciences, 2026)
The total solar eclipse of April 8, 2024 presented a uniquely favorable circumstance for radio science. The Moon’s shadow passed near Canadian time standard station CHU, which transmits in the high frequency (HF, i.e., 3–30 MHz) band. It was therefore possible to observe signal changes due to shifting ionospheric conditions along the path of the eclipse by using CHU as a signal of opportunity. In under 3 months, our undergraduate team developed and deployed low-cost instrumentation to record CHU for timing and amplitude analysis. 18 units were distributed across 6 locations roughly aligned with the eclipse path. Each unit contained a radio recorder which retained time traceability to UTC via GPS time synchronization, allowing capture of the CHU signal with no unbounded error beyond the 50 µs sampling interval. Seven units captured changes in the received signal during the eclipse, most notably a tenfold increase in the signal strength at 7.85 MHz for a unit in Little Rock, AR. Its timing suggests a one-hop propagation path reflecting in the ionosphere over Cleveland, OH. The stations were deployed to and maintained by volunteers contacted through the amateur radio and citizen science community. This campaign demonstrates the accessibility and effectiveness of research using low-cost instrumentation and the power of citizen science.